2004
DOI: 10.1007/s11661-004-0354-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heat treatment on Mg2Si coarsening in aluminum 6105 alloy

Abstract: The coarsening behavior of Mg 2 Si intermetallic particles was studied during homogenization of aluminum 6105 alloy. An industrially homogenized 6105 aluminum alloy contained large globular undissolved Mg 2 Si. With subsequent heat treatment at 590°C over 1 week, it was found that the large Mg 2 Si precipitates coarsened with time. The coarsening of the large Mg 2 Si precipitates was quantified by statistical analysis of micrographs. A linear relationship between and time fits the experimental measurements qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 9 publications
0
23
0
1
Order By: Relevance
“…[40,41] Because of the dissolution and degradation of grain boundary secondary phases, mainly Fe-IMCs, IMC inter-connectivity was also notably reduced after homogenization (Figure 8(c)), with inter-connectivity only maintained by those particles that retained the larger petals around primary a-Al grains, as shown in Figure 15(b). Similarly the platelet-like inter-connected b-AlFeSi breaks into fine disk-like particles during the b-AlFeSi to a c -AlFeSi transformation leaving finer disk-like particles around grains, as also shown in Figure 15(b).…”
Section: B Evolution Of Fe-imcs During Homogenizationmentioning
confidence: 99%
“…[40,41] Because of the dissolution and degradation of grain boundary secondary phases, mainly Fe-IMCs, IMC inter-connectivity was also notably reduced after homogenization (Figure 8(c)), with inter-connectivity only maintained by those particles that retained the larger petals around primary a-Al grains, as shown in Figure 15(b). Similarly the platelet-like inter-connected b-AlFeSi breaks into fine disk-like particles during the b-AlFeSi to a c -AlFeSi transformation leaving finer disk-like particles around grains, as also shown in Figure 15(b).…”
Section: B Evolution Of Fe-imcs During Homogenizationmentioning
confidence: 99%
“…The authors conclude, on the basis of regression analysis, that the results show a particularly strong correlation with n ϭ 3.8 in [1] where t is time at temperature and is the value of at t ϭ 0, suggesting that grain boundary diffusion (n ϭ 4) dominates volume diffusion (n ϭ 3) in the coarsening of these particles. The present purpose is to offer an alternative interpretation of these results.…”
mentioning
confidence: 94%
“…
This interesting article [1] includes measurements of the size distribution, average radius , and volume fraction f of globular Mg 2 Si particles in this Al-Mg-Si alloy vs duration of homogenization treatment for up to 7 days at 590 °C. The authors conclude, on the basis of regression analysis, that the results show a particularly strong correlation with n ϭ 3.8 in [1] where t is time at temperature and is the value of at t ϭ 0, suggesting that grain boundary diffusion (n ϭ 4) dominates volume diffusion (n ϭ 3) in the coarsening of these particles.
…”
mentioning
confidence: 99%
“…However, previous results showed that large globular Mg 2 Si particles in billets of a 6105 alloy, which contains 0.85 wt.% Mg 2 Si, did not dissolve at 590°C which is above its solvus temperature, but instead coarsened with time from 10 mm to 26 mm after heat treatment for 7 days. 12 These results suggest that the actual solvus and solidus temperatures for the 6105 alloy may be higher than indicated in the classic phase diagram. 13 Hence, the solutionizing temperature for a specific alloy should be optimized according to the change in the size of Mg-Si particles after the solution heat treatment.…”
Section: Solutionizing and Precipitation Of Mg-si Particles In 6xxx Smentioning
confidence: 84%